An Investigation of Red Fox (Vulpes vulpes) and Eurasian Badger (Meles meles) Scavenging, Scattering, and Removal of Deer Remains: Forensic Implications and Applications. (25th July 2014) - Young, Alexandria; Márquez‐Grant, Nicholas; Stillman, Richard; Smith, Martin J.; Korstjens, Amanda H.
Abstract: Within northwest Europe, especially the United Kingdom, the red fox ( Vulpes vulpes ) and the Eurasian Badger ( Meles meles ) are the largest wild scavengers capable of modifying a set of remains through scavenging. Knowledge of region‐specific and species‐typical scavenging behaviors of scavengers within the crime scene area and surroundings can aid in more efficient and accurate interpretations. The scavenging behaviors of captive and wild foxes and badgers were recorded and compared through actualistic methods and direct observation. The scavenging by wild foxes and badgers of surface‐deposited baits and whole deer ( Cervus nippon ; Capreolus capreolus ) in a woodland was observed and analyzed. Wild foxes were found to scavenge deer more frequently than badgers. The scavenging of deer remains by foxes was also compared with forensic cases. The scavenging pattern and recovery distances of deer and human remains scavenged by foxes were similar but were potentially affected by the condition and deposition of a body, and the presence of clothing.